2010
DOI: 10.1007/s11606-010-1575-7
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Correlates of Racial Disparities in Adherence to Colorectal Cancer Screening Guidelines

Abstract: OBJECTIVES:We examined the presence and correlates of Black/White racial disparities in adherence to guidelines for colorectal cancer screening (CRCS). METHODS:The sample included 328 Black and 1827 White patients age 50-75 from 24 VA medical facilities who responded to a mailed survey with phone follow-up (response rate: 73% for Blacks and 89% for Whites). CRCS adherence and race were obtained through surveys and supplemented with administrative data. Logistic regressions estimated the contribution of demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 64 publications
1
41
0
Order By: Relevance
“…Finally, we found that African Americans with lung cancer (but not those with colon cancer) were less likely to receive ESA treatment. Race/ethnic differences in processes of care and treatment observed in other populations have often, but not always, been found to be absent or attenuated in VA facilities [36][37][38][39][40][41][42]. We don't know whether the difference was due to unobserved clinical factors, patient preference for other treatments, access issues, or other reasons, and therefore, we cannot make any judgments about its appropriateness.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, we found that African Americans with lung cancer (but not those with colon cancer) were less likely to receive ESA treatment. Race/ethnic differences in processes of care and treatment observed in other populations have often, but not always, been found to be absent or attenuated in VA facilities [36][37][38][39][40][41][42]. We don't know whether the difference was due to unobserved clinical factors, patient preference for other treatments, access issues, or other reasons, and therefore, we cannot make any judgments about its appropriateness.…”
Section: Discussionmentioning
confidence: 98%
“…A sub-analysis in that study pointed to the targeting of screening efforts on unmarried, low income white men and higher income black men whose screening rates were low. 9 Decreasing family income was associated with decreasing colorectal cancer screening rate. 10 This study and its conclusions are limited by its small sample drawn from a single center and the retrospective nature of its design.…”
Section: Univariate Differences Between African Americansmentioning
confidence: 99%
“…For example, a recently published study by Boehmer et al 8 reported that, after adjusting for confounders, there were no racial/ethnic differences in timely one-year CRC screening. Burgess et al 9 found that health disparities in CRC screening are greatly attenuated in the Veteran Affairs system where both Whites and Blacks have substantially higher rates of screening than the national average. A sub-analysis in that study pointed to the targeting of screening efforts on unmarried, low income white men and higher income black men whose screening rates were low.…”
Section: Univariate Differences Between African Americansmentioning
confidence: 99%
“…O ne of the most troubling aspects of US medicine is the level of disparities in health and healthcare outcomes, [1][2][3] While previous work has generally focused on one or two potential contributors, the paper by Kaplan et al examines a myriad of patient, provider and system characteristics to explore the source of disparities in diabetes control among Mexican-Americans. 4 The differences in glycosylated hemoglobin seen between Vietnamese-Americans, non-Hispanic whites and MexicanAmericans were explained by differences in gender, age, duration of diabetes, education and income level and insurance status.…”
mentioning
confidence: 99%